Penerapan IEC/ISO 31010:2019 untuk Manajemen Risiko pada Sistem Informasi Kesejahteraan Sosial-Next Generation - Ericson Malau; Evi Maria (Journal of Information System Research (JOSH), 2023)
This research aims to apply IEC/ISO 31010:2019 in the risk management process in the Batam City social welfare-Next Generation (SIKS-NG) information system. SIKS-NG implementation provides benefits and creates risks that can hinder and harm the Batam City Social Service if a risk management process is not carried out. The stages of risk management in IEC/ISO 31010:2019 include communication and consultation, establishing context, and assessing risk by identifying, analyzing, evaluating, and managing risks. IEC/ISO 31010:2019 was chosen because this standard provides complete and systematic guidance for risk management activities. The research found that 16 possible risks arose when the Batam City Social Service implemented SIKS-NG in the planning process for social assistance there. The 16 potential risks consist of three at a high level, eight at a medium level, and five at a low level. This research adds to evidence that IEC/ISO 31010: 2019 is effective for use as a risk management framework in applications implemented in government agencies. This research also provides suggestions for treating the risks in the SIKS-NG application. It creates risk management documentation to help the Batam City Social Service manage risks arising in this application, especially in the planning process for social assistance.